Rheological evaluation of local clay samples in central region Ghana for oil well drilling fluid formulation - Gomado, Foster; Kobina, Forson; Owusu Boadi, Augustus; Awelisah, Yussif Moro (International Journal of Engineering and Technology, 2018)
The superb rheological features of bentonites makes them an excellent candidate in drilling operations. Its capacity of bentonite to swell and extend to a few times its unique volume gives it the gelling and viscosity controlling quality. The execution of clay or specifical bentonite as a great consistency controlling operator in drilling fluids largely depends on the great extent of its rheological conduct. Ghana as of late found oil and it has tossed a test to research to explore the utilization of local materials in the oil and gas operations. A rheological study was conducted on local clay samples from Ajumako, Saltpond and Winneba in the Central district of Ghana as a viscosifier in drilling muds. This will help to improve the local content of Ghana's oil and gas industry. Drilling muds were prepared from the samples in addition to a control mud using imported non-treated bentonite. The local clay samples were subjected rheological test where the flow behavior of the muds was determined by measuring the gel strength, plastic viscosity, and the yield point. The experimental values were compared to the API standards. It was revealed that the local clay had some potential features of bentonite and could be utilized as controlling operators in drilling fluids provided the clays are beneficiated to enhance their rheological properties. This novel tend to improve the local content in oil and gas industry in Ghana through the deployment of the local materials in oil and gas operations in the nation.